Physical Education Majors Team Teaching in an Early Field Experience in a Junior High School Setting: 體育本科生應用團隊教學法於初中體育課 - BARNEY, David; CHRISTENSON, Robert (Asian Journal of Physical Education & Recreation, 2009)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. The early field experience (EFE) has been considered a valuable and important component of a physical education majors education (Curtner-Smith, 1993). For this study 26 pre-service teachers (PST) (physical education majors) team taught (13 teams) in an EFE in a local junior high school. During their EFE each team taught 2 lessons in the school. From this study it was found that during the PST lessons the junior high students were active in the class activities, that the PST should have used louder voices when teaching, that the PST should have had a back-up plan for their lessons, that music played can help during class activities, and that they PST felt their lessons went “well.” 早期的實習教學經驗，對於體育本科生而言是一種有效的學習方法。是次研究共有26位體育實習教師參與團隊式教學法，結果顯示這種教學法令初中學生更加活躍，而實習教師需要加大他們説話聲音，需要準備後備的活動計劃，在活動中使用適當的音樂等，這些改變能夠讓實習教師感到有滿意的教學效果。